2015
DOI: 10.1080/1540496x.2015.1046339
|View full text |Cite
|
Sign up to set email alerts
|

Investor Attention, Institutional Ownership, and Stock Return: Empirical Evidence from China

Abstract: Zheng, L. (1999). Is money smart? A study of mutual fund investors' fund selection ability. The Journal of Finance, 54(3), 901-933.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Eventually, as for volatility of returns, although risk and return trade-off theory illustrates stocks with higher volatility have higher returns, Ang et al [25] found that Table 8 further suggests that investor attention has a positive and significant effect on stock returns. This result is consistent with either Da, Engelberg, and Gao [22] or Ying, Kong and Luo [31], arguing that higher investor attention can generate a greater buying pressure and thus raise stock prices and the short-term holding period returns. Meanwhile, we find that the media effect is no longer significant after controlling for the measure of investor attention, which is consistent with our earlier hypothesis that the investor attention is the intermediate channel and the key mechanism supporting the positive media effect on stock returns in China's stock market.…”
Section: Further Explanation and Explorationsupporting
confidence: 79%
See 1 more Smart Citation
“…Eventually, as for volatility of returns, although risk and return trade-off theory illustrates stocks with higher volatility have higher returns, Ang et al [25] found that Table 8 further suggests that investor attention has a positive and significant effect on stock returns. This result is consistent with either Da, Engelberg, and Gao [22] or Ying, Kong and Luo [31], arguing that higher investor attention can generate a greater buying pressure and thus raise stock prices and the short-term holding period returns. Meanwhile, we find that the media effect is no longer significant after controlling for the measure of investor attention, which is consistent with our earlier hypothesis that the investor attention is the intermediate channel and the key mechanism supporting the positive media effect on stock returns in China's stock market.…”
Section: Further Explanation and Explorationsupporting
confidence: 79%
“…According to the existing literature [30][31][32], growth stocks with a higher price to equity ratio tend to have attracted more investor attention. To verify the validity of "attention-driven buying" theory to explain our main empirical results, we further test how the effect of media coverage on stock returns differ in stocks with different implied growth level measured by price to equity ratio.…”
Section: Further Explanation and Explorationmentioning
confidence: 99%
“…For example, see Aouadi et al (2013) for France, Bank et al (2011) for Germany, Ying et al (2015) for China, Takeda and Wakao (2014) for Japan, Tantaopas et al (2016) for the Asia-Pacific countries, and Da et al (2011) for the U.S. characteristics (fixed effect) in each country sample, showing that limited investor attention violates the efficient market hypothesis. However, among three attention-stock market activity relationships, only the attention-trading volume relationship is statistically significant for the developing markets.…”
mentioning
confidence: 99%
“…First, 80% of investors in China are individual investors. These investors trade very frequently and are highly short-term oriented (Allen, Qian, & Qian, 2005;Dong & Gou, 2010;Ying, Kong, & Luo, 2015).…”
Section: Further Discussionmentioning
confidence: 99%